Democratic Brazil Divided - Power, Timothy J. (Timothy Joseph), 1962-; Kingstone, Peter R., 1964-; Project Muse. (Pittsburgh, Pa. : University of Pittsburgh Press, 2017)
March 2015 should have been a time of celebration for Brazil, as it marked thirty years of democracy, a newfound global prominence, over a decade of rising economic prosperity, and stable party politics under the rule of the widely admired PT (Workers' Party). Instead, the country descended into protest, economic crisis, impeachment, and deep political division.Democratic Brazil Dividedoffers a comprehensive and nuanced portrayal of long-standing problems that contributed to the emergence of crisis and offers insights into the ways Brazilian democracy has performed well, despite the explosion of crisis. The volume, the third in a series from editors Kingstone and Power, brings together noted scholars to assess the state of Brazilian democracy through analysis of key processes and themes. These include party politics, corruption, the new 'middle classes', human rights, economic policy-making, the origins of protest, education and accountability, and social and environmental policy. Overall, the essays argue that democratic politics in Brazil form a complex mosaic where improvements stand alongside stagnation and regression.
Introduction: a fourth decade of Brazilian democracy: achievements, challenges, and polarization / Peter R. Kingstone and Timothy J. Power -- Part I. The democratic context -- The PT in power, 2003-2016 / Oswaldo E. do Amaral and Rachel Meneguello -- Good government and politics as usual? The schizophrenic path of the Workers' Party / Benjamin Goldfrank and Brian Wampler -- Part II. Policy innovation and state capacity in a maturing democracy -- Corruption and accountability in Brazil / Matthew M. Taylor -- Environmental politics in Brazil: the cross-pressures of democracy, development, and global projection / Kathryn Hochstetler -- Checking the power of mayors: explaining improvements in Brazilian educational outcomes / Marcus Andre Melo -- Assessing the Bolsa familia: successes, shortcomings, and unknowns / Wendy Hunter and Natasha Borges Sugiyama -- Progress or perdition? Brazil's National Truth Commission in comparative perspective / Anthony W. Pereira -- Part III. Politics from the bottom up -- Toward a (poor) middle-class democracy? Upward mobility and politics under Lula and Dilma / Maria Hermania Tavares de Almeida and Fernando Henrique Guarnieri -- The economic context of social protests in 2013 / Alfredo Saad-Filho -- Part IV. Strategies of global projection -- Democracy postponed: a political economy of Brazil's oligarchic foreign policy / Sean Burges and Jean Daudelin -- The public bank trilemma: Brazil's new developmentalism and the BNDES / Leslie Elliott Armijo.
Includes bibliographical references and index.
Description based on print version record.
eBooks on EBSCOhost
Keywords: Brazil -- Social conditions -- 1985-; Brazil -- Politics and government -- 2003-; Political participation -- Brazil; Democracy -- Brazil; Brésil -- Conditions sociales -- 1985-; Brésil -- Politique et gouvernement -- 2003-; Participation politique -- Brésil.; POLITICAL SCIENCE / Essays; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Government / National; POLITICAL SCIENCE / Reference; POLITICAL SCIENCE / World / Caribbean & Latin American; Democracy; Political participation; Politics and government; Social conditions; Brazil; Since 1985; Electronic books